Quality of Life of End Stage Renal Disease Patients Undergoing Dialysis in Southern Part of Kerala, India: Financial Stability and Inter-dialysis Weight Gain as Key Determinants - Kasi Visweswaran; Muhammed Shaffi; Philip Mathew; Minu Abraham; Jinbert Lordson; Premini Rajeev; Reena Thomas; Rajeev Aravindakshan; Jayadevan G; Kesavan Rajasekharan Nayar; Marthanda Pillai (Springer, 2020)
Background: Quality of Life (QoL) reflects the quality and outcome of healthcare along with key indicators of performance such as mortality and morbidity. Objective: The aim of the study was to measure the QoL among patients with End Stage Renal Disease (ESRD) on maintenance hemodialysis and to understand various correlates of QoL. Methods: A total of 95 ESRD patients from three dialysis centres in Southern districts of Kerala were interviewed. QoL was measured using vernacular version of World Health Organization Quality Of Life - Brief Version (WHOQOL-BREF) questionnaire. Results: The mean age of the patients was 56.2 ± 13 years and 73.7% were males. Mean converted scores for overall QoL was 42.37 ± 21.3 and Health-related QoL (HRQoL) was 43.3 ± 18.3, indicating poor QoL. Males had significantly higher physical domain scores (p < 0.03). Occupation, income and Socio-economic Status (SES) influenced overall HRQoL while better income and higher SES predicted better scores in psychological and environmental domains. Conclusion: Patients with better control over inter-dialysis weight gain (≤1600 g) had significantly higher scores. This study highlights the importance of using QoL tools in assessing the QoL of patients and the factors contributing to it.